Ideological influences on the reception of Karl May in Slovenia - Trupej, Janko (Annales. Series historia et sociologia, 2020)
The article discusses the extent to which ideological factors affected Karl May's reception among Slovenians. The analysis encompassed writings about May in Slovenian serial publications from the beginning of the 20th century until the present. The results showed that May's reception during a particular historical period was influenced by both the ideological orientation of the serial publication in which the writer was discussed, which is especially characteristic of the Habsburg era, and the contemporary socio-political situation in the country of which the Slovenian territory formed part at a particular time, which is most true for the socialist era.
Keywords: German literature; ideologija; ideology; May, Karl; nemška književnost; recepcija; reception; trivial literature; trivialna književnost